Efektivitas Metode Problem-Based Learning Terhadap Hasil Belajar Siswa pada Pelajaran Dasar Teknik Ketenagalistrikan - Indah Mulia Hati; Usmeldi Usmeldi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This research aims to determine the effectiveness of the Problem-Based Learning method on the learning outcomes of Basic Electrical Engineering Students in class X at SMKN 1 Pariaman. Learning using the Problem-Based Learning method has not shown significant changes in student learning development. Therefore, students do not appear to have the skills to express thoughts, opinions, and ideas and digest the discussion topics presented, thus influencing student learning outcomes in the cognitive domain. Therefore, it is necessary to research the effectiveness of the Problem-Based Learning method to see its effectiveness on student learning outcomes. This research uses a type of experimental research which is categorized into a type pf quasi-experimental research using two classes, namely the experimental and control classes. The subjects of this research were students in class to measure this effectiveness, a pretest was given before implementing Problem-Based Learning. The posttest is given after the Basic Electrical Engineering learning process. The post-test results will be analyzed using tests such as classical completeness and effect size. The test results show that the scores of students who apply Problem-Based learning are better than those who do not apply Problem-Based Learning. There was an increase in student learning outcomes after implementing Problem-Based Learning. So Problem-Based learning is effective in improving student learning outcomes.